Screening for inborn errors of metabolism among newborns with metabolic disturbance and/or neurological manifestations without determined cause - Oliveira, Allan Chiaratti de; Santos, Amélia Miyashiro Nunes dos; Martins, Ana Maria; D’Almeida, Vâniia (São Paulo Medical Journal, 2001)
CONTEXT: Inborn Errors of Metabolism are hereditary affections resulting from incompetence inenzymatic reactions of intermediary metabolism. At present, several hundred hereditary metabolic disturbances are known, many of which correspond to severe life-threateningdisorders. OBJECTIVE:The early detection of carriers has motivated the screening for the sedisturbance samong newborns at the Neonatal Unit of Hospital São Paulo, in an attempt toinitiate support treatment,when available, before clinical manifestations become evident. DESIGN: Prospective study of risk patients. SETTING: Laboratory for Inborn Errors of Metabolism at the Center for Medical Genetics of the Departments of Pediatrics and Morphology of Universidade Federal de São Paulo/Escola Paulista de Medicina. Newborn care unit atatertiary care hospital. PARTICIPANTS: 101 children admitted into the Neonatal Unit were included in this study by presenting hypoglycemia, metabolic acidosis, jaundice, difficulty in gaining weight, diarrhea, vomiting, hepato-and/or splenomegaly, cataracts, apnea, convulsions, hypo- or hypertonia. DIAGNOSTIC TESTS: Tests routinely utilized, performed for qualitative research of abnormal substances excreted in the urine in situations of metabolic disorder. RESULTS: Children were included in the study mainly because of presenting hypoglycemia, jaundice and metabolicacidosis. Sixty-four newborns presente dat least one positive test result. Most of the positivity was due to transitory metabolic alterations of the newborn, such as the case of Transitory Neonatal Tyrosinemia, presented by 29 patients. Nine infants were referred to the Center for Medical Genetics of Universidade Federal de São Paulo for continuation of the diagnostic investigation. For three of them, the test sapplied permitted us to formulatea diagnostic hypothesis of mucopolysaccharidosis, tyrosinemia typeIandnon-ketotichyperglycinemia, respectively. CONCLUSIONS: The high positivity observed in the tests reflects the newborn’s ownmetabolicimmaturity. The selection of 9% of the studied cases for out patient follow- up confirms that Inborn Errors of Metabolism must be suspected whenever a patient presents metabolic disturbances or neurological manifestations with out a determined cause. They should be research edinparallel with the other diagnostic possibilities and not just taken to be exceptional diagnoses.